Brand Heritage: Telaah Identitas Merek dan Persepsi Konsumen - Adman Nursal (Jurnal Manajemen dan Bisnis Madani, 2021)
As a relatively new thing, the concept of brand heritage is starting to attract the attention of marketing researchers. Several concepts that emerged later, both from the perspective of brand identity and perceived brand, criticized the previous concepts. By reviewing the literature, this article views, from a brand identity perspective, the elements of brand heritage proposed by Urde et al. (2007) is the most appropriate concept to describe the phenomenon. From the perceived brand perspective, the omniporal perceived brand heritage scale and the perceived brand heritage scale based on heritage aspects are both relevant, but it is proposed to rename them into brand heritage image and perceived brand heritage, respectively. This theoretical study also offers a matrix of conceptual brand heritage categories that is useful as a roadmap for further research.